2010
DOI: 10.1007/s00247-010-1596-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of whole liver and small region-of-interest measurements of MRI liver R2* in children with iron overload

Abstract: Background Measurement of liver MRI T2* and R2* is emerging as a reliable alternative to liver biopsy for the quantitation of liver iron content. A systematic investigation of the influence of the region of interest size and placement has not been conducted. Objective To compare small and whole liver region of interest (ROI) MRI R2* values to each other and to biopsy liver iron content in patients with iron overload. Materials and Methods Forty-one iron-overloaded patients, ages 7 to 35 years, underwent bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 36 publications
1
65
0
Order By: Relevance
“…They concluded that the single ROI approach can be safely used in the clinical area when taking care to avoid susceptibility artifact effect. McCarville et al evaluated 41 patients with iron overload by R2* mapping and correlated the results with liver biopsy [16]. In their study they compared small ROI placement and a whole liver method.…”
mentioning
confidence: 99%
“…They concluded that the single ROI approach can be safely used in the clinical area when taking care to avoid susceptibility artifact effect. McCarville et al evaluated 41 patients with iron overload by R2* mapping and correlated the results with liver biopsy [16]. In their study they compared small ROI placement and a whole liver method.…”
mentioning
confidence: 99%
“…McCarville et al showed that whole-liver R2* map is less subject to interreviewer discordance compared to R2* analysis drawn by multiple ROIs in liver. They proposed using R2* maps for quantification of liver iron content instead of biopsy in patients with hepatic iron overload (34).…”
Section: Discussionmentioning
confidence: 99%
“…Off-line image analysis was performed on a computer workstation using a graphical user interface (GUI) developed in MATLAB (The MathWorks Inc., Natick, MA) [30]. For the entire image, pixel-wise T2* values were calculated by fitting a monoexponential decay to the magnitude of the mGRE signal while accounting for Rician noise bias [31, 32].…”
Section: Methodsmentioning
confidence: 99%
“…in images that showed the main portal vein as described in [30]: (i) Small regions of interest (ROIs) were drawn on the T2*-weighted source images or T2* maps in a homogenous region of liver parenchyma excluding large biliary and vascular structures in the right lobe of the liver. This ROI position was selected as described in [30] to ensure that no bias was introduced in the HIC calculation. The average T2* was subsequently calculated across all pixels within the ROI and the resulting R2* (=1/T2*) was recorded.…”
Section: Methodsmentioning
confidence: 99%